Identifying the target, mechanism, and agonist of α-ketoglutaric acid in delaying mesenchymal stem cell senescence - Zhao Cui; Jiameng Li; Caifeng Li; Shiwen Deng; Wei Liu; Tong Lei; Junxian Cao; Ziyi Wang; Xiaoxu Wang; Shuhua Ma; Yinhua Zhu; Hongjun Yang; et al. (Cell Reports, 2025)
Summary: α-ketoglutaric acid (AKG), a tricarboxylic acid cycle metabolite central to aerobic metabolism and longevity, retains unresolved anti-aging protein targets. Here, we demonstrate that reduced isocitrate dehydrogenase 1 (IDH1) expression during senescence lowers AKG production, accelerating the aging of mesenchymal stem cells (MSCs). Exogenous AKG or IDH1 overexpression restores AKG levels, enabling 2-oxoglutarate and Fe(II)-dependent oxygenase domain-containing protein 1 (OGFOD1)-catalyzed hydroxylation of ribosomal protein S23 (RPS23) at proline 62. Mechanistically, AKG stabilizes the OGFOD1-RPS23 complex, enhancing translation accuracy to limit misfolded protein accumulation while sustaining synthesis rates, thereby balancing proteostasis. The natural flavonoid scutellarin (Scu), identified as an IDH1 agonist, elevates AKG to delay MSC senescence. In aged mice, Scu improves cognitive function, reduces osteoporosis and skin aging, and suppresses senescence-associated secretory phenotype. Our findings identify the AKG-IDH1-RPS23 axis as a regulator of stem cell senescence and we propose metabolic reprogramming strategies for anti-aging therapies.